Anxiety Is Associated With DPPIV Alterations in Children With Selective Mutism and Social Anxiety Disorder: A Pilot Study - Golub, Yulia; Stonawski, Valeska; Plank, Anne C.; Eichler, Anna; Kratz, Oliver; Waltes, Regina; von Hoersten, Stephan; Roessner, Veit; Freitag, Christine M. (Frontiers in Psychiatry, 2021)
Background: Both selective mutism (SM) and social anxiety disorder (SAD) are severe pediatric anxiety disorders with the common trait of behavioral inhibition (BI). The underlying pathophysiology of these disorders remains poorly understood, however converging evidence suggests that alterations in several peripheral molecular pathways might be involved. In a pilot study, we investigated alterations in plasma molecular markers (dipeptidyl peptidase-4 [DPPIV], interleukin-6 [IL-6], tumor necrosis factor-β [TNF-β] and neuropeptide-Y [NPY]) in children with SM, SAD and healthy controls, as well as the correlation of these markers to symptom severity. Methods: We included 51 children and adolescents (aged 5-18 years; n = 29 girls): n = 20 children in the SM-, n = 16 in the SAD- and n = 15 in the control-group (CG). Peripheral blood samples were analyzed for DPPIV, IL-6, TNF-β and NPY concentrations. Diverse psychometric measures were used for BI, anxiety and mutism symptoms. Results: Lower DPPIV-levels were correlated with more anxiety symptoms. However, we could not find a difference in any molecular marker between the patients with SAD and SM in comparison to the CG. Conclusion: DPPIV is proposed as relevant marker for child and adolescent anxiety. Investigating the pathophysiology of SM and SAD focusing on state and trait variables as anxiety or BI might help better understanding the underlying mechanisms of these disorders. Further studies with especially larger cohorts are needed to validate the current pilot-findings